Three-Dimensional Manipulation for Self-Focusing Behavior via the State of Polarization - Lu, Lu; Wang, Zhiqiang; Lin, Rong; Cai, Yangjian (Frontiers in Physics, 2022)
In this work, the controllable self-focusing behavior is first investigated by manipulating the state of polarization (SoP), that is, the phase difference between two polarized components at the initial optical field, which can be used to realize the three-dimensional manipulation of self-focusing behavior. Furthermore, the properties of self-focusing propagation (including intensity distribution, propagation dynamics, and Stokes parameters) are researched in detail, which are beneficial to select the reasonable initial SoP for further theoretical and experimental exploration. Particularly, the radially polarized beam as a laser source not only prolongs the self-focusing length but also improves the power density of self-focusing spots on the target. These findings may have potential in the multidimensional optical manipulation, the optical information transmission, the high-power long-range laser atmospheric propagation, and related applications.